2015
DOI: 10.3390/ijms16034865
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties and Structure Analysis of a DAG-Like Lipase from Malassezia globosa

Abstract: Diacylglycerol (DAG)-like lipases are found to play an important role in the life sciences and industrial fields. A putative DAG-like lipase (MgMDL2) from Malassezia globosa was cloned and expressed in recombinant Pichia pastoris. The recombinant MgMDL2 was expressed as a glycosylated protein and purified into homogeneity by anion exchange chromatography. The activity of recombinant MgMDL2 was optimal at 15 °C and pH 6.0, and it keeps over 50% of relative activity at 5 °C, suggesting that MgMDL2 was a cold act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…However, no family class 3 lipase showed a significant activity with triolein. This observation is not surprising, as MgLip1 and MgMDL2, belonging to the family class 3 lipases, have been reported to be active with MAGs and DAGs only Xu et al, 2015). As TAG is a key component of human sebum, these results suggest…”
Section: Substrate Specificities Of M Globosa Lipasesmentioning
confidence: 51%
See 4 more Smart Citations
“…However, no family class 3 lipase showed a significant activity with triolein. This observation is not surprising, as MgLip1 and MgMDL2, belonging to the family class 3 lipases, have been reported to be active with MAGs and DAGs only Xu et al, 2015). As TAG is a key component of human sebum, these results suggest…”
Section: Substrate Specificities Of M Globosa Lipasesmentioning
confidence: 51%
“…During expression in P. pastoris, a majority (70 to 90 %) of the Asn residues in potential N-glycosylation sites will be modified by glycosylation (Skropeta et al, 2007). N-Glycosylation was previously shown for heterologously expressed MgLip1 and MgMDL2 from P. pastoris cells (Xu et al, 2012b(Xu et al, , 2015, and N-glycosylation has also been shown to be a post-translation modification in M. globosa as MgLip2 purified from M. globosa also exhibited a larger molecular mass than expected (55 vs 49.5 kDa). MALDI-TOF MS analysis of the purified protein confirmed the identity as MgLip2 (Juntachai et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations